Primitivism and modern art - Rhodes, Colin (World of art, 1994)
Summary:A fascination with the primitive lies at the heart of some of the most influential developments in Westem art produced between 1890 and 1950 - a time that witnessed both the heroic period of modern art and the apogee and decline of the West's colonial power. Many groups have been labelled primitive, including the so-called tribal peoples from Africa, Oceania and North America, but also prehistoric cultures, European peasants, the insane and children. Through the lens of their own society, many modern artists looked both to the art and to the worldview of the primitive as a means of challenging established beliefs, but the primitive to which they turned was as varied as the movements of modern art.